THE IMPLEMENTATION OF LAND MORTGAGE BASED ON POWER OF ATTORNEY TO GRANT LAND MORTGAGE (SKMHT) AND LAND MORTGAGE DEED (APHT) AT NOTARY AND LAND DEED OFFICIAL (PPAT) YONDRI DARTO, S.H. - Utari Afnesia; Lu Sudirman (Universitas Internasional Batam, 2022)
Security rights of land are expected to be a strong security institution which can provide legal certainty. Security rights are done through the making of APHT, where the grantor of the rights himself comes directly to the PPAT or he can also use SKMHT made by a notary or PPAT as the basis for the APHT. The existence of these provisions basically implies that SKMHT is mandatorily made using an authentic deed. If SKMHT does not substantially meet the provisions required by UUHT, the legal consequences are the void of SKMHT by law and the PPAT is prohibited to make the APHT. Furthermore, if the SKMHT made by a notary does not meet the conditions stipulated in UUJN the legal consequences are that the strength of its evidence becomes a deed under the hand. If this happens, indeed the APHT made by PPAT based on SKMHT cannot be registered. That is because, the 2 SKMHT which forms the basis of making APHT violates the conditions implied in UUHT that is created by an authentic deed, so consequently the principle publicity of security rightsarenot fulfilled.